Optimization of extraction and spray drying processes of Tongkat Ali extracts using response surface methodology - Wan Zamri, Wan Mastura (2014)
Tongkat Ali is a popular herb due to its various medicinal benefits. However, Tongkat Ali processing has a low yield and the quality and safety of spray dried Tongkat Ali had been an issue. Therefore, this study was done to optimize Tongkat Ali production process to obtain high quality and safe Tongkat Ali product. A Central Composite Design was employed to study the effects of solvent to raw material ratio, duration of extraction and particle size of raw material from Tongkat Ali extraction on total solid content and amount of eurycomanone. A Box Benhken Design was applied to determine the effects of inlet air temperature, feed temperature, air pressure and feed flow rate from Tongkat Ali spray drying process on the efficiency of spray drying. Effect of spray drying heat was investigated on four bioactive compounds of Tongkat Ali which were amount of eurycomanone, total polysaccharide, total protein, and total glycosaponins and its toxicity. The optimum condition for extraction process was achieved at 10:1 g/g of solvent to raw material ratio,1 hour of duration of extraction and 0.5-1.0 mm particle size which corresponded to 6.2290 mg/g solid content and 1.7139 % eurycomanone. Yield of extract at this condition was 6.8526 %. For spray drying process, the optimum condition was observed at 180 °C of inlet air temperature, 100 °C of feed temperature, 15.18 psi of air pressure and 5.44 ml/min of feed flowrate with 38.48 % efficiency of spray drying achieved.Temperature of the spray dryer was found to have no effect on the amount of eurycomanone, total polysaccharide, total glycosaponins and cytotoxicity except for total protein. Spray dried Tongkat Ali was safe to be used and no major difference was found in the cytotoxic test of both spray dried and freeze dried extracts. Response surface methodology was successful in identifying the optimal conditions of Tongkat Ali processing.